The Effect of Accommodation and Restaurant Service Quality on Tourist Interests in Visiting the City of Tidore Islands - Yudian, Rais A; Dewi, Liliana; Choerunisa, Siti (Akademi Komunitas MAPINDO, 2023)
As one of the important aspects in supporting the accommodation and restaurant business. Aautomatically, application of quality of service must be applied by all restaurants and accommodations anywhere, including restaurants and accommodation in the Tidore City. Because, as an area that is trying to improve and develop its tourism sector, of course, the implementation of service quality must be given special attention. Moreover, the quality of service is one of the important factors that affect the interest of visiting tourists to one tourist destination. However, the problem that occurs in the accommodation and restaurant sector in Tidore Islands City is that the level of awareness of the manager regarding the importance of quality of service has not been very good. This certainly greatly affects the interest of tourists visiting in the city of Tidore Islands. This research aims to look at the quality of accommodation services and the quality of restaurant services on their influence on tourist interests. The research method is a quantitative method, where researchers spread questionnaires about the quality of accommodation and restaurant services in Tidore City, so that it can be concluded that the good quality of service greatly affects the interest in tourists visiting. Keywords: Quality of service, Accommodation, Restaurants, Tourist Visiting Interest, Tidore Islands CityKeywords: Quality of service, Accommodation, Restaurants, Tourist Visiting Interest, Tidore Islands City